A transdisciplinary approach to growing an applied science of cultural evolution for a sustainable future - Brooks J; Koomen R; Søgaard Jørgensen P; Berl REW; Chávez-Páez W; Eirdosh D; Abdul Hakim M; Hanisch S; Lindell C; Liu JH; Nguyen M-HT; Pisor A; et al. (The Royal Society, 2025)
Addressing sustainability challenges requires an integrative approach that bridges scientific research with practical application. The field of cultural evolution (CE) offers a perspective that may guide transitions and cultural transformations for a sustainable future. However, there have been few efforts to apply this field to sustainability challenges. This study explores how CE can inform sustainability practices through mechanisms of social learning, processes of cultural adaptation and conditions that promote cooperative governance. Through a two-phase research design-comprising online discussions with professionals from six domains, and an international workshop-we examined the perceived benefits, challenges and opportunities for applying CE in real-world contexts. Our findings indicate that professionals recognize CE's potential to enhance knowledge dissemination, foster adaptation to social-ecological changes, improve governance structures and generate cooperation. However, barriers such as complex terminology, unfamiliarity with CE, the lack of clear, context-specific evidence of added value and competition with existing frameworks hinder its application. To overcome these challenges, we propose simplifying CE concepts, demonstrating its unique contributions, and continuing to foster co-production with practitioners to refine its applicability. This study is an initial step in building an applied science of CE that can support sustainability transformations across diverse domains. This article is part of the theme issue 'Transforming cultural evolution research and its application to global futures'.
Keywords: knowledge co-production; sustainability transformations; social learning; cultural adaptation; governance; cooperation; social–ecological systems; cultural change; socio-technical transitions